Relationship between pneumonitis induced by immune checkpoint inhibitors and the underlying parenchymal status: a retrospective study. Issue 1 (16th March 2020) - Pozzessere, Chiara; Bouchaab, Hasna; Jumeau, Raphael; Letovanec, Igor; Daccord, Cécile; Bourhis, Jean; Prior, John O.; Peters, Solange; Lazor, Romain; Beigelman-Aubry, Catherine
In patients with primary or secondary lung tumour treated with immune checkpoint inhibitors, immune-related pneumonitis is a rare adverse event but may evolve to respiratory failure. Prompt management is required and usually consists of treatment interruption and immunosuppressive drug administration. The aim of this study was to evaluate relationships between immune-related pneumonitis and pre-existing parenchymal status, especially tumour location and history of chest radiotherapy. Computed tomography (CT) scans of patients with immune-related pneumonitis were retrospectively reviewed. Pattern, distribution and extent of pneumonitis were assessed in six lung regions. In patients who received radiotherapy, the extent of pneumonitis was evaluated according to the radiation field. Among 253 patients treated with immunotherapy, 15 cases of immune-related pneumonitis were identified. 10 had previous or concomitant chest radiotherapy in addition to immunotherapy. At CT scan, 29 (33%) out of 88 regions encompassed the primary tumour (n=4), a lung metastasis (n=4) and/or radiation fields (n=21). A significantly higher prevalence of parenchymal involvement by immune-related pneumonitis occurred within areas of primary or metastatic malignancy and/or radiation field (97%) as compared to other areas (3%, p=0.009). Lung regions affected by the primary tumour, metastasis or radiotherapy had a higher probability of immune-related pneumonitis than others (OR 10.8, p=0.024). An organising pneumonia (OP) pattern was more frequent after radiotherapy (70% versus 0%, p=0.024), whereas nonspecific interstitial pneumonia features were more commonly seen in radiotherapy-naive patients (100% versus 10%, p=0.002). In patients with primary or secondary lung tumour treated with immune checkpoint inhibitors, immune-related pneumonitis is preferentially located within lung areas involved by tumour and/or radiation fields. In patients with primary or secondary lung tumour treated by immune checkpoint inhibitors, immune-related pneumonitis induced by these agents is preferentially located within lung areas involved by tumour and/or radiation fields http://bit.ly/2NJZmGx